2011
DOI: 10.1111/j.1755-5949.2011.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐Based Cognitive Therapy for Nonremitted Patients with Bipolar Disorder

Abstract: Introduction Bipolar disorder is characterized by recurrent episodes of depression and/or mania along with inter-episodic mood symptoms that interfere with psychosocial functioning. Despite periods of symptomatic recovery, many individuals with bipolar disorder continue to experience substantial residual mood symptoms that often lead to the recurrence of mood episodes. Aims The present study explored whether a new mindfulness-based cognitive therapy (MBCT) for bipolar disorder would increase mindfulness, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 80 publications
4
115
0
6
Order By: Relevance
“…Baer et al (2006) cautioned that the FFMQ "requires extensive additional validation in a range of samples" (p43); yet, to date, the factor structure of the English-version of the FFMQ has not been assessed using any clinical samples. This is an important omission given that the FFMQ has begun to be used in studies to assess change pre-to post-MBIs for clinical conditions (e.g., Bowen & Kurz, 2012;Deckersbach et al, 2012;McManus et al, 2012;Vollestad et al, 2011). For example, in the context of MBCT, the factor structure of the FFMQ has not been assessed using a sample of individuals who suffer from recurrent depression, thus suggesting caution regarding its use within clinical research or as a clinical tool to assess treatment change.…”
Section: The Five Facet Mindfulness Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Baer et al (2006) cautioned that the FFMQ "requires extensive additional validation in a range of samples" (p43); yet, to date, the factor structure of the English-version of the FFMQ has not been assessed using any clinical samples. This is an important omission given that the FFMQ has begun to be used in studies to assess change pre-to post-MBIs for clinical conditions (e.g., Bowen & Kurz, 2012;Deckersbach et al, 2012;McManus et al, 2012;Vollestad et al, 2011). For example, in the context of MBCT, the factor structure of the FFMQ has not been assessed using a sample of individuals who suffer from recurrent depression, thus suggesting caution regarding its use within clinical research or as a clinical tool to assess treatment change.…”
Section: The Five Facet Mindfulness Questionnairementioning
confidence: 99%
“…The FFMQ has begun to be used in studies to assess change pre-to post-MBIs for a variety of clinical conditions (e.g., Bowen & Kurz, 2012;Deckersbach et al, 2012;McManus et al, 2012;Vollestad et al, 2012). In particular, MBCT is a psychotherapeutic intervention which was specifically developed for the prevention of recurrent depression in people who are not currently suffering from depression.…”
Section: Five Facet Mindfulness Questionnairementioning
confidence: 99%
“…However, a later study of MBCT for bipolar disorder (n = 15) reported no significant differences between preand post-treatment mania and depression scores (22). Another study examining the effects at 3-month follow-up noted improvements in depression symptoms, psychological wellbeing, and psychosocial functioning (23).…”
Section: Introductionmentioning
confidence: 99%
“…56 The benefits seen by MBT could be potentially attributed to a number of causes, not just an increase in the patient's mindfulness, for example interaction with the therapist or group support. One of the causes of this deficit is the lack of control groups in much of the research included in this review (see for example Craigie et al, 28 Evans et al, 29 Deckersbach et al 34 and Hofmann et al, 18 whose meta-analyses of 39 studies included only 16 studies with a control group. In addition, the type of control group used is also important.…”
Section: Key Pointsmentioning
confidence: 99%
“…In contrast, Weber et al 33 used MBCT in remitted patients with bipolar disorder and found that overall, there were no significant improvements in mindfulness, depression and hypomania between the beginning and end of the MBCT programme. Deckersbach et al 34 found that non-remitted bipolar patients who received MBCT had improved mindfulness, residual depressive mood symptoms and psycho social functioning at …”
Section: Mbt For Patients With Mood and Anxiety Disordersmentioning
confidence: 99%